Paradigma Maslahat: Menyeimbangkan Hak Asasi Manusia dan Otoritas Negara dalam Perspektif Politik Hukum Islam - Ahmad Al Fairuz Ramadhan; A.Muh Agil Fikri Firdaus; Kurniati (Al-Istinbath : Jurnal Ilmu Hukum dan Hukum Keluarga Islam, 2026)
This study aims to analyze the political morality of Islamic law in balancing human rights (HAM) with state interests, focusing on the policy of restricting congregational worship in Indonesia during the Covid-19 pandemic. Previous studies generally discuss the relationship between human rights and Islamic law conceptually and generally or assess the legitimacy of pandemic policies solely from the perspective of positive constitutional law. Consequently, there is a conceptual gap regarding how the political morality of Islamic law can be used as a measurable assessment instrument for the legitimacy of human rights restriction policies. This study uses a normative legal method with a conceptual and statutory approach, analyzed descriptively and qualitatively using deductive reasoning on primary and secondary legal materials. The novelty of this study lies in the construction of five assessment indicators—protective objectives, proportionality, temporary nature, participation of religious authorities, and legitimate legal basis—derived from the Maqasid al-Shari'ah principle to test the harmony of state regulations. The results of the study indicate that the policy of restricting worship in Government Regulation Number 21 of 2020, Regulation of the Minister of Health Number 9 of 2020, and Fatwa of the Indonesian Ulema Council Number 14 of 2020 is substantively in line with four of the five indicators, but is weak in the indicator of a valid legal basis because it is regulated through regulations under the law, not a law as required by Article 28J paragraph (2) of the 1945 Constitution. The conclusion of the study confirms that the political morality of Islamic law provides ethical legitimacy for the restriction of human rights for the sake of hifdz an-nafs, but this legitimacy is only complete if accompanied by adequate legal certainty. The implication of this study is the need to strengthen the legislative framework for public health emergencies at the level of law and institutionalize the involvement of religious authorities in the formulation of human rights restriction policies in the future. Abstrak Penelitian ini bertujuan untuk menganalisis moral politik hukum Islam dalam menyeimbangkan Hak Asasi Manusia (HAM) dengan kepentingan negara, dengan memfokuskan kajian pada kebijakan pembatasan ibadah berjemaah di Indonesia selama pandemi Covid-19. Kajian terdahulu umumnya membahas relasi HAM dan hukum Islam secara konseptual-umum atau menilai keabsahan kebijakan pandemi semata dari perspektif hukum tata negara positif, sehingga terdapat kesenjangan konseptual mengenai bagaimana moral politik hukum Islam dapat dijadikan instrumen penilaian yang terukur atas legitimasi kebijakan pembatasan HAM. Penelitian ini menggunakan metode hukum normatif dengan pendekatan konseptual dan pendekatan perundang-undangan, dianalisis secara deskriptif-kualitatif dengan nalar deduktif atas bahan hukum primer dan sekunder. Kebaruan penelitian ini terletak pada konstruksi lima indikator penilaian—tujuan perlindungan, proporsionalitas, sifat sementara, partisipasi otoritas keagamaan, dan dasar hukum yang sah—yang diturunkan dari prinsip Maqasid al-Syari’ah untuk menguji keselarasan regulasi negara. Hasil penelitian menunjukkan bahwa kebijakan pembatasan ibadah dalam Peraturan Pemerintah Nomor 21 Tahun 2020, Peraturan Menteri Kesehatan Nomor 9 Tahun 2020, dan Fatwa Majelis Ulama Indonesia Nomor 14 Tahun 2020 secara substantif selaras dengan empat dari lima indikator tersebut, tetapi lemah pada indikator dasar hukum yang sah karena diatur melalui peraturan di bawah undang-undang, bukan undang-undang sebagaimana disyaratkan Pasal 28J ayat (2) UUD 1945. Simpulan penelitian menegaskan bahwa moral politik hukum Islam memberi legitimasi etis bagi pembatasan HAM demi hifdz an-nafs, tetapi legitimasi tersebut hanya utuh apabila disertai kepastian bentuk hukum yang memadai. Implikasi penelitian ini adalah perlunya penguatan kerangka legislasi kedaruratan kesehatan masyarakat setingkat undang-undang serta pelembagaan keterlibatan otoritas keagamaan dalam perumusan kebijakan pembatasan HAM pada masa mendatang.